Membedah Isu 'Peringatan Darurat' di Media Online yang Paling Banyak Dibaca dan Dipercaya di Indonesia - Alvin, Silvanus (Jurnal Spektrum Komunikasi, 2024)
This paper explores how online news outlets in Indonesia have covered the "Peringatan Darurat Garuda Biru" movement. By employing a corpus-assisted discourse analysis (CADS), the study examines how language and media framing subtly direct blame toward the DPR and the Jokowi administration for the perceived democratic backsliding and manipulations of election laws. A total of 68 news articles from two major online media, Detik.com and CNNIndonesia.com, published between August 21-22, 2024, were analyzed. Detik.com was selected due to its highest media reach in Indonesia, while CNN Indonesia was chosen for its high level of public trust. The data processing was conducted using Voyant Tools, focusing on frequency, concordance, and collocation analyses. The research reveals that terms such as "manuver DPR" and "RUU Pilkada" are frequently used in association with political manipulation, while "Jokowi" appears as a central figure, reflecting broader concerns over governance and democracy. The analysis shows how online discourse implicitly assigns accountability, shaping public opinion without explicit accusations. Based on these findings, it can be concluded that online news outlets in Indonesia do not report the Peringatan Darurat issue in a neutral manner but have a pro-democracy stance.